2000
DOI: 10.1042/cs0980303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adenosine receptor antagonists on the responses to contrast media in the isolated rat kidney

Abstract: Contrast media can induce both a decrease in renal blood flow and a reduction in glomerular filtration rate (GFR) when administered to both experimental animals and humans. In the present study we have examined the role of adenosine in mediating these effects using the isolated perfused rat kidney. Kidneys were perfused with a 6. 7%-(w/v)-albumin-based perfusate supplemented with glucose and amino acids (n=6 per group). They were exposed to diatrizoate [20 mg of iodine (mgI)/ml; osmolality 1650 mOsm/kg of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 39 publications
(71 reference statements)
1
13
0
2
Order By: Relevance
“…In pilot experiments (unpublished observations), we have used a combination of a selective adenosine A 1 -receptor antagonist (DPCPX) and a selective endothelin ET-A receptor antagonist (BQ123) prior to CM injection, but this did not either prevent the CM-induced hypoperfusion. The results are in line with those of Oldroyd et al [13] showing that CM-induced depression in renal plasma flow is not attributable to adenosine. The CM-induced reduction in GFR was in that study shown to be mediated by adenosine independent of a change in vascular resistance and possibly secondary to mesangial cell contraction.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In pilot experiments (unpublished observations), we have used a combination of a selective adenosine A 1 -receptor antagonist (DPCPX) and a selective endothelin ET-A receptor antagonist (BQ123) prior to CM injection, but this did not either prevent the CM-induced hypoperfusion. The results are in line with those of Oldroyd et al [13] showing that CM-induced depression in renal plasma flow is not attributable to adenosine. The CM-induced reduction in GFR was in that study shown to be mediated by adenosine independent of a change in vascular resistance and possibly secondary to mesangial cell contraction.…”
Section: Discussionsupporting
confidence: 92%
“…The CM may directly stimulate renal vasoconstrictor receptors, release renal vasoconstrictors, inhibit renal vasodilators, induce formation of oxygen-derived free radicals or change physical factors. Some of the factors potentially involved are: the renin-angiotensin system [17]; prostaglandins [18]; calcium [19]; nitric oxide [20]; and adenosine [13,14,16,21]. Furthermore, the high osmolarity [22] and the viscosity [23] of the CM have an effect on renal haemodynamics which may include changes in renal interstitial pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine is an important intrarenal mediator, which can induce a decrease in the glomerular filtration rate through vasoconstriction of the afferent arterioles and contraction of the mesangial cells of the glomeruli (Oldroyd et al 2000). Adenosine also induces vasoconstriction in the renal cortex and vasodilatation in the renal medulla, increases the generation of oxygen-free radical cells, and is a mediator of the tubuloglomerular feedback (TGF) response.…”
Section: Pharmacological Manipulationmentioning
confidence: 99%
“…Moreover, the general reduction in renal plasma flow and GFR caused by CM is not attributable to enhanced adenosine action. 60 CM can also have direct cytotoxic effects on renal tubular cells. A perturbation of mitochondrial enzyme activity and mitochondrial membrane potential is found under ex vivo conditions in a proximal tubule cell line.…”
Section: Mechanisms Of Cinmentioning
confidence: 99%